STUDI TENTANG PERAN ORANG TUA DALAM MEMBIMBING ANAK SELAMA PEMBELAJARAN TATAP MUKA MASA NEW NORMAL PADA SISWA SMPN 1 KAMPAR UTARA - Hasanah, Fitria; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The background of this research was the phenomenon that emerged in a pre-survey that was previously conducted in March 2021 on students of SMPN 1 Kampar Utara. The formulation of the problem is the role of parents in guiding children in face-to-face learning during the new normal for students of SMPN 1 Kampar Utara. The purpose of this study was to find out the role of parents in guiding children in face-to-face learning during the new normal for students of SMPN 1 Kampar Utara. The method of this research was descriptive quantitative research. The instrument of data collection in this research was a questionnaire that consisted of 25 statements and interviews. The population of this research consisted of 66 respondents from 66 samples. It was determined by using a saturated sampling technique (census sampling). Based on the results of the research, it can be concluded that the data of the role of parents in guiding children in face-to-face learning during the new normal period at SMPN 1 Kampar Utara was categorized in the